Federal Worker Protection Standard key definitions - McDonald, S. K., author; Hofsteen, L. M., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet defines terms used in the Worker Protection Standard (WPS).
Federal Worker Protection Standard
CEPEP 6/03, updated 6/06.
This fact sheet was revised as part of the Comprehensive Worker Protection Standard Awareness Project for Colorado.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Labeling; Agricultural chemicals -- Government policy; Pesticide applicators (Persons) -- Health and hygiene